Avaliação de metaloproteinases de matriz -2, -9 e timp-2 em polpas dentais humanas sadias e inflamadas - Accorsi-Mendonça, Thais, 1977- (2009)
Orientadores: Alexandre Augusto Zaia, Sergio Roberto Peres Line